Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let's simplify the expression [tex]\(6 + \sqrt{-80}\)[/tex] step-by-step.
1. Identify the square root of a negative number:
[tex]\[ \sqrt{-80} \][/tex]
To deal with the square root of a negative number, we use the imaginary unit [tex]\(i\)[/tex], where [tex]\(i = \sqrt{-1}\)[/tex]. Thus, we can rewrite [tex]\(\sqrt{-80}\)[/tex] as:
[tex]\[ \sqrt{-80} = \sqrt{80} \cdot \sqrt{-1} = \sqrt{80} \cdot i \][/tex]
2. Simplify the square root of 80:
Let's break down 80 into its prime factors:
[tex]\[ 80 = 16 \cdot 5 \][/tex]
Now, we can use the property of square roots that [tex]\(\sqrt{a \cdot b} = \sqrt{a} \cdot \sqrt{b}\)[/tex], which gives us:
[tex]\[ \sqrt{80} = \sqrt{16 \cdot 5} = \sqrt{16} \cdot \sqrt{5} = 4 \sqrt{5} \][/tex]
3. Combine the results from the previous steps:
[tex]\[ \sqrt{-80} = 4 \sqrt{5} \cdot i \][/tex]
4. Add this to the original expression:
[tex]\[ 6 + \sqrt{-80} = 6 + 4 \sqrt{5} \cdot i \][/tex]
Thus, the simplified form of [tex]\(6 + \sqrt{-80}\)[/tex] is:
[tex]\[ 6 + 4 \sqrt{5}i \][/tex]
1. Identify the square root of a negative number:
[tex]\[ \sqrt{-80} \][/tex]
To deal with the square root of a negative number, we use the imaginary unit [tex]\(i\)[/tex], where [tex]\(i = \sqrt{-1}\)[/tex]. Thus, we can rewrite [tex]\(\sqrt{-80}\)[/tex] as:
[tex]\[ \sqrt{-80} = \sqrt{80} \cdot \sqrt{-1} = \sqrt{80} \cdot i \][/tex]
2. Simplify the square root of 80:
Let's break down 80 into its prime factors:
[tex]\[ 80 = 16 \cdot 5 \][/tex]
Now, we can use the property of square roots that [tex]\(\sqrt{a \cdot b} = \sqrt{a} \cdot \sqrt{b}\)[/tex], which gives us:
[tex]\[ \sqrt{80} = \sqrt{16 \cdot 5} = \sqrt{16} \cdot \sqrt{5} = 4 \sqrt{5} \][/tex]
3. Combine the results from the previous steps:
[tex]\[ \sqrt{-80} = 4 \sqrt{5} \cdot i \][/tex]
4. Add this to the original expression:
[tex]\[ 6 + \sqrt{-80} = 6 + 4 \sqrt{5} \cdot i \][/tex]
Thus, the simplified form of [tex]\(6 + \sqrt{-80}\)[/tex] is:
[tex]\[ 6 + 4 \sqrt{5}i \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.